Major Modes of Variability - Roy, I (Springer, 2018)
This chapter focused on major modes of variability which serve the key role in controlling the regional climate. In terms of tropospheric variability, it defined and discussed ENSO (El Niño Southern Oscillation), NAO (North Atlantic Oscillation), AO and AAO (Arctic Oscillation, Antarctic Oscillation), Indian Monsoon, Indian Ocean Dipole (IOD), PDO (Pacific Decadal Oscillation) and AMO (Atlantic Multidecadal Oscillation). Later it attended stratosphere variability; this constitutes QBO (quasi-biennial oscillation) and SSW (stratospheric sudden warming). Main characteristic features of each of these modes were elaborately discussed.